2019
DOI: 10.1177/0022427819859638
|View full text |Cite
|
Sign up to set email alerts
|

Examining the (Dis)Agreement between Etiology and Consequences of Adults’ and Youths’ Perceptions of Collective Efficacy in Boston

Abstract: Objectives: To examine the extent to which adults’ and youths’ perceptions of collective efficacy align, the shared and unique correlates of adults’ and youths’ perceptions, and the effects of adults’ and youths’ perceptions on youths’ violence. Method: Descriptive analysis, hierarchical linear modeling, and spatial analysis analyze 1,636 youths from the 2008 Boston Youth Survey and 1,677 adults distributed across 85 neighborhoods from the 2008 Boston Neighborhood Study. Results: Descriptive analysis indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Their findings show that youth-perceived collective efficacy is associated with less violent attitudes, but parents’ perceptions of collective efficacy are not. Tucker and colleagues (2019) found that youth-perceived collective efficacy, rather than neighborhood collective efficacy as evaluated by local adults, is responsible for driving juvenile delinquency. Gearhart (2019b) found that parent- and youth-perceived social cohesion and informal social control did not significantly predict lower levels of self-reported juvenile delinquency.…”
Section: Collective Efficacy Theorymentioning
confidence: 95%
See 4 more Smart Citations
“…Their findings show that youth-perceived collective efficacy is associated with less violent attitudes, but parents’ perceptions of collective efficacy are not. Tucker and colleagues (2019) found that youth-perceived collective efficacy, rather than neighborhood collective efficacy as evaluated by local adults, is responsible for driving juvenile delinquency. Gearhart (2019b) found that parent- and youth-perceived social cohesion and informal social control did not significantly predict lower levels of self-reported juvenile delinquency.…”
Section: Collective Efficacy Theorymentioning
confidence: 95%
“…Research also suggests that the strength of perceived collective efficacy, as well as its relationship with outcomes, varies depending on whether it is measured from the perspective of an adult, or the perspective of a child (Gearhart, 2019b; Johnson et al, 2011; Simons et al, 2005; Tucker et al, 2019). For example, Simons and colleagues (2005) found that youth and parent collective efficacy is associated with more authoritative parenting, which in turn prevents youth from interacting with delinquent peers and performing delinquent acts.…”
Section: Collective Efficacy Theorymentioning
confidence: 99%
See 3 more Smart Citations